1996
DOI: 10.3109/03009749609065649
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Rheumatoid Arthritis on Psychological Distress

Abstract: The objective of our study was to estimate the impact of early rheumatoid arthritis (RA) on psychological distress by comparing patients with RA and matched controls. A sample of 238 patients (age 20-70 years, mean age 52 yrs) with RA of 0 to 4 years duration (mean 2.2 yrs), was compared to 116 control persons matched to the patients with respect to sex, age, and geographic area. Data were collected through self-report questionnaires. Patients with RA rated their mental health significantly lower than the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 17 publications
4
18
0
2
Order By: Relevance
“…Fernandez and Milburn (1994) found the affective component of pain to be a linear function of three differentially weighted sets of emotion (anger, fear, and sadness) in a study of chronic pain patients. Smedstad et al (1996;1997), in their studies of the relationship between pain and distress in Rheumatoid Arthritis patients, found evidence that both variables influence each other, i.e. whereas distress proved to be a significant predictor of pain, increase in distress was found to be a secondary consequence of increased pain.…”
mentioning
confidence: 92%
“…Fernandez and Milburn (1994) found the affective component of pain to be a linear function of three differentially weighted sets of emotion (anger, fear, and sadness) in a study of chronic pain patients. Smedstad et al (1996;1997), in their studies of the relationship between pain and distress in Rheumatoid Arthritis patients, found evidence that both variables influence each other, i.e. whereas distress proved to be a significant predictor of pain, increase in distress was found to be a secondary consequence of increased pain.…”
mentioning
confidence: 92%
“…Most studies of depression have been done in established RA, although some recent reports have concerned EIA [24,25,26,27,28,29]. Several of the reports concern the same group of patients [25,26,27, 30], so only a modest amount of work about depression has actually been done in EIA. Nonetheless, Smedstad et al [27] compared 238 patients who had RA for 4 years or less to matched controls and found that 22% had ‘possible depression’, and 11% had ‘probable depression’.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of early pharmacological and multidisciplinary team interventions aim to alter the infl ammatory process, reduce symptoms and enhance self-management (Hilliquin and Menkes, 1994). At diagnosis, people with RA may experience not only a range of physical problems, such as pain, disability and fatigue, but also associated emotional consequences, including depressive symptoms and anxiety (Ramjeet et al, 2005;Scott et al, 2005;Smedstad et al, 1996;Van der Heide et al, 1994). Unpredictability disrupts life plans, increasing psychological distress and helplessness, and roles and relationships come under stress (Newman et al, 1996;Ryan, 1996).…”
mentioning
confidence: 99%